RETROSPECTIVE AND CURRENT ATTITUDE OF COACHES TO A SPORTS PSYCHOLOGIST - Khvatskaya E.E.; Korshunova O.V.; Fatsievich-Slinchenko A.V.; Bryntseva E.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the attitude of coaches to the activities of a sports psychologist in the context of the psychological support of a sports reserve, as well as the actual "request" of coaches to improve psychological competence. Methods and structure of the study. A survey was conducted in the form of a questionnaire, in which coaches in various sports of the North-West of Russia took part (St. Petersburg, Leningrad Region, Murmansk, Arkhangelsk, Vologda): retrospectively in 2016 - 222 (130 men and 92 women, average age - 37 years, average experience - 16.5 years), actual in 2022 - 143 (75 men and 68 women, average age - 41 years, average experience - 18 years). 64 trainers took part in the assessment of preferences for topics to improve psychological competence (2022, 2023). Fisher’s test was used to assess the significance of differences. Results and conclusions. The trend of ambiguous attitude of coaches to the activities of a sports psychologist persists. More than a third of coaches (2022) are ready to turn to a psychologist on their own to work with an athlete (team) and almost all are ready to recommend parents to athletes, if necessary, contact this specialist. Retrospectively and currently, the positive attitude of coaches towards a sports psychologist is associated with a constructive experience of interaction, including through increasing psychological competence with the help of this specialist, as well as with effective help to athletes (team) through parents’ appeal to a psychologist with the consent (on the recommendation) of the coach.